(untitled) (Baghdad Science Journal, 2005)
The oyster ??????? (planned) (Pallas) of lesions that have entered Iraq recently became spyware severe damage in more than a station from power plants in Iraq, including the power plant in Mussayab Vamahar accumulates in pipes cooling and disrupts their work Vtafrtf heat systems cooling and thereby determiningefficiency and lead to added cost many cleaning or replacement of damaged parts